Zinc Enhances Long-Term Potentiation Through p2x Receptor Modulation in the Hippocampal ca1 Region - Morales-Munoz, B; Rozas-Salas, C; Zeise-Ssa., M (2011)
Zn2+ is an essential ion that is stored in and co-released from glutamatergic synapses and it modulates neurotransmitter receptors involved in long-term potentiation (LTP). However, the mechanism(s) underlying Zn2+-induced modulation of LTP remain(s) unclear. As the purinergic P2X receptors are relevant targets for Zn2+ action, we have studied their role in LTP modulation by Zn2+ in the CA1 region of rat hippocampal slices. Induction of LTP in the presence of Zn2+ revealed a biphasic effect - 5-50?m enhanced LTP induction, whereas 100-300?m Zn2+ inhibited LTP. The involvement of a purinergic mechanism is supported by the fact that application of the P2X receptor antagonists 2 ,3 -O-(2,4,6-trinitrophenyl) ATP (TNP-ATP) and periodate-oxidized ATP fully abolished the facilitatory effect of Zn2+. Notably, application of the P2X7 receptor-specific antagonist Brilliant Blue G did not modify the Zn2+-dependent facilitation of LTP. Exogenous ATP also produced a biphasic effect - 0.1-1?m ATP facilitated LTP, whereas 5-10?m inhibited LTP. The facilitatory effect of ATP was abolished by the application of TNP-ATP and was modified in the presence of 5?m Zn2+, suggesting that P2X receptors are involved in LTP induction and that Zn2+ leads to an increase in the affinity of P2X receptors for ATP. The latter confirms our previous results from heterologous expression systems. Collectively, our results indicate that Zn2+ at low concentrations enhances LTP by modulating P2X receptors. Although it is not yet clear which purinergic receptor subtype(s) is responsible for these effects on LTP, the data presented here suggest that P2X4 but not P2X7 is involved. © 2011 The Authors. European Journal of Neuroscience © 2011 Federation of European Neuroscience Societies and Blackwell Publishing Ltd.